How Effective is Digital-Assisted CTL for Mathematical Reasoning? A Systematic Literature Review - Siti Nurhaliza; Heris Hendriana; Anik Yuliani; Riki Candra ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2026)
The integration of digital technology in mathematics education is essential for addressing challenges in students’ mathematical reasoning and engagement. This study systematically reviews the effectiveness of Contextual Teaching and Learning (CTL) assisted by digital tools, specifically Thinglink and Kahoot, in enhancing students’ mathematical reasoning skills and learning activeness. Following the Systematic Literature Review (SLR) framework, this research analyzed national and international journal articles published over the last decade, selected through predefined inclusion criteria. Data were qualitatively synthesized to identify instructional strategies and evaluate reported learning outcomes across diverse educational settings. Findings indicate that the CTL approach significantly fosters critical thinking and problem-solving abilities by bridging abstract concepts with real-world contexts. Specifically, Thinglink facilitates contextual understanding through interactive visual media, while Kahoot enhances learning activeness through game-based assessment. The synergy between CTL and these digital tools creates a student-centered environment that promotes active participation and deeper conceptual mastery. In conclusion, CTL assisted by Thinglink and Kahoot is an effective strategy for improving mathematical reasoning and student engagement, providing a robust model for innovative mathematics instruction in the digital era.